MENILIK BUDAYA PENJARA: TEORI STRUKTURAL FUNGSIONAL EMILE DURKHEIM - Ciek Julyati Hisyam; Dian Jesica Simanjuntak; Fadia Tuffahati; Itsna Fakhria; Muharomah Ayu Safaatun; Rohmatul Amaliyah Al-Fauziah (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
Prison culture is a term addressed to correctional institutions that have their own rules that are different from the rules of society outside prison. The purpose of the research is to explain the life of prisoners in prison, build relationships between prisoners and prisoners with warders, through the values and norms that exist in prison and shape the behavior of these prisoners. The research method is descriptive through a qualitative approach with data collection techniques through in-depth interviews with informants in the prison. The results of the study state that the existing culture in prison is part of a social system that forms a unity with its respective functions, in line with Emile Durkheim's structural functionalism theory.